Islamic-Based Change Management Leadership: Strategy and Management - Nur Marliana Anggraini; Nuri Aslami (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to analyze Islamic-based leadership strategies and their management within an organization. Currently, changes occur quickly, and make demands on every organization to be able to make changes so as not to be left behind. To deal with changes that take place quickly, every organization needs an effective leadership strategy in order to achieve success in managing change. In an Islamic perspective, leadership is not just an activity to manage resources so as to achieve a desired goal, but involves Islamic principles and values. Through literature review and conceptual analysis, this research was able to identify relevant Islamic values ​​and principles related to leadership and organizational change. This research has revealed that the strategies that can be applied in managing change based on Islam are by conducting effective communication, strong or sturdy leadership, managing resistance, developing employee skills, and creating a conducive work environment. The results of this study indicate that the integrity of Islamic values ​​in leadership strategies has a positive impact in shaping ethical organizational culture, increasing employee involvement in the organization, and strengthening organizational identity. By conducting effective communication and consultation with members of the organization will create success in an Islamic-based leadership strategy. This research can provide a deeper understanding of Islamic-based leadership strategies in change. Applying Islamic values ​​in the culture and strategies within an organization will create an ethical organizational environment in accordance with the foundation of Islamic law.